Antibody-based proteomics to identify an apoptosis signature for early recurrence of hepatocellular carcinoma. Issue 1 (December 2016) - Morofuji, Noriaki; Ojima, Hidenori; Hiraoka, Nobuyoshi; Okusaka, Takuji; Esaki, Minoru; Nara, Satoshi; Shimada, Kazuaki; Kishi, Yoshiro; Kondo, Tadashi
Abstract Background Early recurrence after surgical resection is a hallmark of poor prognosis in hepatocellular carcinoma (HCC). To determine the proteomic background of early recurrence of HCC, we focused on apoptosis-related proteins. Methods Surgically resected tumor tissues were obtained from 80 patients, including HCC tumor tissues, non-tumor tissues, and normal liver tissues. These samples were grouped in the discovery and validation sample sets. The expression level of 192 apoptosis-related proteins was monitored using 247 commercially available antibodies and western blotting. The intensity of protein bands was compared between the tumor and non-tumor tissues as well as between the patients who had recurrence within 2 years after surgery and those who did not. Results In the first screening, we used pooled samples. The intensity of 53 protein bands detected by 37 unique antibodies was higher in tumor tissues compared with normal liver tissues, especially tumor tissues from patients who had recurrence within 2 years after surgery. In the second screening, we examined individual samples used to make the pooled samples. Among the selected bands and antibodies, the intensity of 18 protein bands detected by 11 antibodies was higher in tumor tissues compared with that in normal tissues, especially tumor tissues from the patients with early recurrence after surgery. For the third screening, we examined the samples from newly enrolled patients using these 11 antibodies. Eighteen protein bands detected by six antibodies were selected by using the same criteria. The corresponding antigens included ERK1, PKG, Apaf1, BclX, phosphorylated c-abl, and PIASx1/2. Conclusions We screened 192 apoptosis-related proteins using specific antibodies and western blotting. We identified 6 apoptosis-related proteins associated with carcinogenesis and early recurrence in HCC. The biological and clinical significance of the identified proteins are worth further investigation.